Evaluation of Annona muricata Acetogenins as Potential Anti-SARS-CoV-2 Agents Through Computational Approaches - Prasad, Shashanka K.; Pradeep, Sushma; Shimavallu, Chandan; Kollur, Shiva Prasad; Syed, Asad; Marraiki, Najat; Egbuna, Chukwuebuka; Gaman, Mihnea-Alexandru; Kosakowska, Olga; Cho, William C.; Patrick-Iwuanyanwu, Kingsley Chukwuemeka; Ortega Castro, Joaquín; et al. (Frontiers in Chemistry, 2021)
Annona muricata, a tropical plant variety has been extensively used in ethnomedicine to treat a wide range of diseases, from malaria to cancer. The plant has been reported to demonstrate significant antiviral properties against the human immunodeficiency virus, herpes simplex virus, human papilloma virus, hepatitis C virus and dengue virus. Additionally, the bioactive compounds responsible for antiviral efficacy have also shown to be selectively cytotoxic while inhibiting tumorigenic cell growth without affecting the normal cell growth. Annonaceous Acetogenins are a class of bioactive compounds exclusive to the Annonaceae family to which the plant A. muricata belongs. In the current study we have created a library of Acetogenins unique to the plant, comprising of Annomuricin A, Annomuricin B, Annomuricin C, Muricatocin C, Muricatacin, cis-Annonacin, Annonacin-10-one, cis-Goniothalamicin, Arianacin and Javoricin, for in silico and theoretical evaluations against the SARS-CoV-2 spike protein in an attempt towards promotion of plant based drug development for the current pandemic of coronavirus disease 2019 (COVID-19). We found that all the Acetogenins showing in silico spike protein significantly docking with good binding affinities. Moreover, it may be regarded that the A. muricata Acetogenins can be evaluated further in vitro and in vivo to identify potent anti-SARS-CoV-2 agents.